2001
DOI: 10.1128/aem.67.4.1783-1787.2001
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Gene Cloning of Purine Nucleosidase from Ochrobactrum anthropi

Abstract: A bacterium, Ochrobactrum anthropi, produced a large amount of a nucleosidase when cultivated with purine nucleosides. The nucleosidase was purified to homogeneity. The enzyme has a molecular weight of about 170,000 and consists of four identical subunits. It specifically catalyzes the irreversible N-riboside hydrolysis of purine nucleosides, the K m values being 11.8 to 56.3 M. The optimal activity temperature and pH were 50°C and pH 4.5 to 6.5, respectively. Pyrimidine nucleosides, purine and pyrimidine nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Nucleoside phosphorylase activities resulting in N-riboside cleavage of purine nucleosides have been identified in various organisms (29). We observed that feeding xanthosine to our yeast cultures results in the production of xanthine, a product synthesized through riboside cleavage of xanthosine.…”
Section: Component Modularity Enables Implementation Of Ribozymementioning
confidence: 65%
“…Nucleoside phosphorylase activities resulting in N-riboside cleavage of purine nucleosides have been identified in various organisms (29). We observed that feeding xanthosine to our yeast cultures results in the production of xanthine, a product synthesized through riboside cleavage of xanthosine.…”
Section: Component Modularity Enables Implementation Of Ribozymementioning
confidence: 65%
“…We first investigated the quaternary structure of recombinant TTHA0556 because the purine nucleosidases so far examined are reported to form dimers, tetramers, and pentamers. [6][7][8][9][10][11] An assay mixture containing the purified MBP-fused recombinant (Fig. 2) with a calculated molecular mass of 66.3 kDa (MBP; 42.5 kDa, TTHA0556; 23.8 kDa) was subjected to gel filtration.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9]12) Various bases and compounds, which were used to examine substrate specificity, as described above, were tested at a final concentration of 0.5 mM under standard assay conditions. Of these, only hypoxanthine showed an inhibitory effect, and this was weak (the specific activity fell to approximately 80% of that without the additive).…”
Section: Effects Of Metalsmentioning
confidence: 99%
“…7) As part of this trend, the microbial metabolism of nucleosides has been intensively investigated. [8][9][10][11][12] The first reaction in nucleoside metabolism is N-riboside cleavage. Two kinds of enzymes, nucleosidase (nucleoside hydrolase; EC 3.2.2.-) and nucleoside phosphorylase (EC 2.4.2.-), are known to catalyze this reaction (Fig.…”
Section: Overview Of Microbial Nucleoside Metabolismmentioning
confidence: 99%